2020
DOI: 10.3390/s20195601
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Graphene-Based Flexible Humidity Sensor

Abstract: Graphene is a new type of carbon material with a flexible, two-dimensional structure. Due to the excellent stability of its lattice structure and its mechanical flexibility, graphene-based materials can be applied in flexible humidity sensors. At present, the application of graphene-based flexible humidity sensors in the fields of medical care and environmental monitoring is attracting widespread attention. In this review, the basic properties of graphene oxide (GO) and reduced graphene oxide (rGO) as moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 87 publications
0
30
0
Order By: Relevance
“…The existence of defects and subsequent formation of various oxygen functional groups are responsible for the remarkable adsorption of water molecules on the GO surface. The details are discussed in the sensing mechanism section 43 , 44 .
Figure 4 Graphene oxide characterizations, ( a ) Raman spectra, and ( b ) FT-IR analysis.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of defects and subsequent formation of various oxygen functional groups are responsible for the remarkable adsorption of water molecules on the GO surface. The details are discussed in the sensing mechanism section 43 , 44 .
Figure 4 Graphene oxide characterizations, ( a ) Raman spectra, and ( b ) FT-IR analysis.
…”
Section: Resultsmentioning
confidence: 99%
“…Among them, reduced graphene oxide (rGO) and graphene oxide (GO) hold great potential for sensing due to the existence of different functional groups on their surface. Particularly, GO is considered as one of the best-known materials for water vapors detection due to the existence of a large number of oxygen functional groups on its surface and edges 44 , 47 . For our study, the electrically insulated GO droplets were deposited onto a highly conductive Si resonator surface and dried at 45 °C for 30–45 min followed by direct sensing characterizations without further annealing.…”
Section: Resultsmentioning
confidence: 99%
“…(ii) Water is a small molecule and, especially at higher humidity levels, can intercalate between individual graphene layers in a single flake or between whole flakes. This causes an increase in the distance between the individual layers in a graphene flake or an increase in the distance between flakes, thus increasing the resistance of the entire layer [25]. These two phenomena can have a synergistic effect at high humidity values.…”
Section: Humidity Sensor Samplesmentioning
confidence: 99%
“…A GQDs-based humidity sensor was also designed by citric acid carbonation and found that GQDs have an exceptional ability to detect the ratio between the quantity of water vapor pressure in the air at a selected temperature and the same amount needed to be saturated at the same temperature at lower relative humidity levels for different humidity levels of RH [144].…”
Section: Humidity Sensormentioning
confidence: 99%
“…water vapor pressure in the air at a selected temperature and the same amount needed to be saturated at the same temperature at lower relative humidity levels for different humidity levels of RH [144].…”
Section: Humidity Sensormentioning
confidence: 99%